2018
DOI: 10.1111/jar.12535
|View full text |Cite
|
Sign up to set email alerts
|

An intervention using the Parenting Toolkit “Children—What does it involve?” and the Real‐Care‐Baby simulator among students with intellectual disability—A feasibility study

Abstract: Background There is limited knowledge about how young people with intellectual disability can be facilitated in their process of deciding about parenthood. This study aimed to evaluate the feasibility of an upcoming trial to evaluate an intervention using the Toolkit “Children—what does it involve?” and the “Real‐Care‐Baby” (RCB) simulator among students with intellectual disability. Methods Six students with intellectual disability participated in an intervention with eight educational sessions and a 3‐day ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 31 publications
(37 reference statements)
2
20
0
Order By: Relevance
“…Even though sexuality education is mandatory in the Swedish school system, evaluations have shown that the quality sometimes is sub-standard [31]. The staff suggested more interactive and hands-on education with adapted tools, in line with a recently published pilot study [32], where an adapted toolkit "Childrenwhat does it involve?" and a Real Care Baby simulator were used.…”
Section: Discussionmentioning
confidence: 91%
“…Even though sexuality education is mandatory in the Swedish school system, evaluations have shown that the quality sometimes is sub-standard [31]. The staff suggested more interactive and hands-on education with adapted tools, in line with a recently published pilot study [32], where an adapted toolkit "Childrenwhat does it involve?" and a Real Care Baby simulator were used.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, these studies have demonstrated the importance of providing real experiences in parenting skills to complement adapted knowledge as a basis for informed decisions and insights. A previous school‐based pilot study found that adapted knowledge about parenting can be combined with actual experiences in caring for a Real‐Care‐Baby (RCB) simulator and the combination can be used for people with ID (Janeslätt, Larsson, Wickström, Springer, & Höglund, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…No study (except the pilot study by Janeslätt et al., 2019) has evaluated the RCB simulator in young individuals with ID. Using an RCB simulator was a way to give young persons with ID concrete experiences of the basic needs of a child.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations